Cooperative Learning Group for English Teachers: One Way of Supporting Under-qualified Teachers - Rahayu, Puji (English Education Department, Universitas Islam Indonesia, 2007)
The fact that English teachers in Indonesia especially in remote area are under qualified is not debatable/They are not only incapable of teaching well but quite a lot of them also still need help in their English proficiency. Asking them to take an English class for them is almost impossible. There must be ways of developing their professionalism while they are performing as teachers.Building a cooperative learning group for English teacher will make them improved in both the knowledge and skills in teaching because of the very slogan of cooperative learning, which is